A world of seclusion: Alcina, Gretchen and Lily - Brokenicky, Janie (Kansas State University, 2012)
This document is focused on three excerpts from a graduate vocal recital, completed in partial fulfillment of the requirements for the Master of Music degree. The recital was held on January 23, 2012 at seven-thirty o’clock in the evening at All Faiths Chapel on the campus of Kansas State University. Selections for this recital were selected upon the theme of Seclusion. The three characters examined further in the document are Alcina in the G. F. Handel opera, Alcina (HWV 34), Gretchen in German Lieder Gretchen am Spinnrade (D. 118) by Franz Schubert, and Lily from the Tony Award-winning Broadway musical, The Secret Garden, by Lucy Simon and Marsha Norman. Each chapter, devoted to a specific work, contains the following: 1) biographical information on the composer, 2) textual analysis, and 3) compositional, stylistic, and technical considerations.
Keywords: Vocal Recital; Seclusion; Alcina; Gretchen; Lily; Music (0413); Musical Performances (0943)